Contents of Elements in Some Flooded Soils as Related to Their Origins in Northeast Thailand - Suphicha Thanachit; Anchalee Suddhiprakarn; Irb Kheoruenromne; R.J. Gilkes (Agriculture and Natural Resources, 2007)
The contents of elements in two flooded soils in Northeast Thailand were studied. Aeric Endoaqualf (P1) was derived from fine-grained sedimentary rocks and Typic Endoaquert (P2) developed on basalt. The concentration of elements (Ti, Fe, Ca, Mg, K, Mn, P, Li, Cs, As, Cr, V, Ni, Rb, Cu, Zn, Ga, Co, Pb, Mo, Zr, U, Sr) in the fine-earth, sand, silt and clay fractions was measured by using XRF and ICP-MS techniques. The results revealed that both soils were deep and alkaline. The 2:1 phyllosilicate clay dominated in clay fraction with minor amount of kaolin. Illite and smectite were major clay minerals in P1 and P2, respectively, which were influenced by their parent materials. Authigenesis of clay and carbonate was evident. The amount of elements was quite low throughout the profiles. This was probably due to the shallow water table and these soils had been saturated with water where the reducing condition restricted the weathering rate of the parent rocks. Additionally, there was limited vertical leaching as compared to lateral water flow. However, P1 showed a larger variation of element compositions than did P2, reflecting a more uniform composition of basalt. The distribution of elements showed that their concentrations were generally high in the clay fraction indicating that the clay played an important role as a reservoir for these elements and heavy metals in soils.